(untitled) (Mantichora. Italian Journal of Performance Studies, 2020)
This paper analyzes how some women authors have re-written Antigone, Sophocles’ tragedy, with particular emphasis on women’s role in the political context. From Liliana Cavani’s film I Cannibali (1969) and Griselda Gambaro’s play Antígona Furiosa (1986), it aims to highlight the performative dimension of Creon’s and Antigone’s speech acts, taking Antigone’s claim by Judith Butler as a theoretical framework. In addition, the contribution draws attention to the ambiguity and complexity of this tragedy. It also reinterprets the rigid opposition between Creon and Antigone, thereby reconsidering the values they have in common as well as their complementary gender roles.